2018
DOI: 10.1002/jrsm.1304
|View full text |Cite
|
Sign up to set email alerts
|

Statistical approaches to adjusting weights for dependent arms in network meta‐analysis

Abstract: Network meta-analysis compares multiple treatments in terms of their efficacy and harm by including evidence from randomized controlled trials. Most clinical trials use parallel design, where patients are randomly allocated to different treatments and receive only 1 treatment. However, some trials use within person designs such as split-body, split-mouth, and crossover designs, where each patient may receive more than one treatment. Data from treatment arms within these trials are no longer independent, so the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The result for fixed effects model, shown in Table , is identical to that of Su and Tu except a few second decimal digits, which is likely due to round‐off errors and the fact that the mvmeta package used by Su and Tu demands that users enter contrast data using treatment A as reference treatment, so artificial data must be imputed for studies that did not include treatment A . The estimated effect depended on r , especially for contrast AE . The result for random effects model (Table ) indicated that the value of r can also influence the estimate of heterogeneity estimate τ 2 .…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…The result for fixed effects model, shown in Table , is identical to that of Su and Tu except a few second decimal digits, which is likely due to round‐off errors and the fact that the mvmeta package used by Su and Tu demands that users enter contrast data using treatment A as reference treatment, so artificial data must be imputed for studies that did not include treatment A . The estimated effect depended on r , especially for contrast AE . The result for random effects model (Table ) indicated that the value of r can also influence the estimate of heterogeneity estimate τ 2 .…”
Section: Resultsmentioning
confidence: 65%
“…Consequently, the outcomes of treatment arms are correlated. Recently, Su and Tu proposed three methods of data manipulation to account for within‐study correlations before routines such as mvmeta in R and STATA can be used to undertake NMA of the Lu‐Ades contrast‐based model . Under the arm‐parameterized SEM framework, the correlation can be easily specified and requires no prior data manipulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk ratios were used to measure the relative treatment effect on the risk of first-attempt insertion failure (failed or successful) and the occurrence of postoperative sore throat (yes/no), weighted mean differences were used to measure changes in OLP (cmH 2 O). For crossover trials, we used the adjusting variance approach to address correlations between different procedures within trials 22 . We evaluated the transitivity assumption by comparing the distribution of NMBAs used across studies.…”
Section: Methodsmentioning
confidence: 99%
“…This renders it difficult, however, to synthesize the evidence using NMA because the independence assumption does not hold. Correlation between data can be adjusted by the standard approach, the reducing weight approach, and the adjusting variance approach [ 9 ].…”
Section: Introductionmentioning
confidence: 99%